Determinan Tunneling Incentive dan Mekanisme Bonus Terhadap Keputusan Perusahaan untuk Melakukan Transfer Pricing - Yunda Riana; Nera Marinda Machdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Factors affecting tunneling incentives and bonus mechanisms in corporate transfer pricing decisions are analyzed in this study. The motivation to place capacity from a branch office to a head office is called tunneling incentives, which will be influenced by transfer pricing decisions. In addition, the way managers determine transfer prices can be influenced by the bonus mechanisms implemented in the company. A qualitative descriptive method with a literature review approach is used in this study. The results of this study show that there is a different relationship between tunneling incentives and bonus mechanisms in transfer pricing decisions, so there is no clear agreement. Important insights into the factors affecting transfer pricing practices are provided to stakeholders by these findings, as well as their impact on the transparency and accountability of financial statements. This study is expected to be used as a reference for further research and provide recommendations for companies in formulating more effective transfer pricing policies. In addition, this study presents detailed illustrations based on existing facts to assist future research by considering tunneling incentives and bonus mechanisms in the context of transfer pricing.